Light-emitting properties of Si-ion-irradiated SiO2/Si/SiO2 layers - Kim, HB; Son, JH; Whang, CN; Chae, KH; Lee, WS; Im, S; Kim, SO; Woo, JJ; Song, JH (KOREAN PHYSICAL SOC, 2000)
Photoluminescence (PL) from a Si-ion-irradiated SiO2/Si/SiO2 layer on a Si substrate at room temperature has been studied to elucidate the luminescence behavior under various post-annealing treatments. A luminescence band around 450 nm is observed from the as-irradiated sample, This luminescence band is found to originate from the diamagnetic defect, known as the B-2 band, generated by Si ion irradiation. The intensity of tills band increases with the increasing annealing temperature up to a critical temperature after Si irradiation. The B-2 Land activates at a lower temperature than the radiative defect related to the PL peak around 600 nm. After tilts ion-irradiated samples are annealed at 1100 degrees C, the PL peaks around 450 nm and 600 nm originating from radiative defects disappear, and a new PL peak appears around 720 nm. This luminescence band is associated with the similar to 5-nm-sized Si nanocrystals produced along the Si layer between SiO2 layers. as determined by high resolution transmission electron microscopy. The intensity of the pi, peak fr om the ion-irradiated SiO2/Si/SiO2 laver is stronger than that from the Si-implanted SiO2 film and that from the SiO2/Si/SiO2 layer annealed without Si irradiation.
Keywords: NANOCRYSTALLINE-SILICON; IMPLANTED SIO2; PHOTOLUMINESCENCE; FILMS; LUMINESCENCE; TEMPERATURE; MATRIX